2014
DOI: 10.1254/jphs.13242fp
|View full text |Cite
|
Sign up to set email alerts
|

Potential Involvement of μ-Opioid Receptor Dysregulation on the Reduced Antinociception of Morphine in the Inflammatory Pain State in Mice

Abstract: Abstract. The antinociceptive effect of morphine in the inflammatory pain state was described in the von Frey filament test using the complete Freund's adjuvant (CFA)-induced mouse inflammatory pain model. After an i.pl. injection of CFA, mechanical allodynia was observed in the ipsilateral paw. The antinociceptive effect of morphine injected s.c. and i.t. against mechanical allodynia was reduced bilaterally at 1 day and 4 days after the CFA pretreatment. The expression level of mRNA for m-opioid receptors at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…This model differs from neuropathic pain because the hyperalgesia is deeply associated with inflammation; furthermore, there is no time for healing of the pathologic tissues. CFA-induced behavioral changes are usually observed in animals after 3 days (early phase); then they typically continue for at least 3 weeks (Ohsawa et al, 2000;Hong et al, 2009;Aoki et al, 2014b). In the present study, strong hypersensitivity to heat and mechanical responses were characterized by a reduction in paw withdrawal latencies between day 3 and day 7.…”
Section: Discussionmentioning
confidence: 48%
“…This model differs from neuropathic pain because the hyperalgesia is deeply associated with inflammation; furthermore, there is no time for healing of the pathologic tissues. CFA-induced behavioral changes are usually observed in animals after 3 days (early phase); then they typically continue for at least 3 weeks (Ohsawa et al, 2000;Hong et al, 2009;Aoki et al, 2014b). In the present study, strong hypersensitivity to heat and mechanical responses were characterized by a reduction in paw withdrawal latencies between day 3 and day 7.…”
Section: Discussionmentioning
confidence: 48%
“…However, in a clinical study, morphine was found to be less effective against inflammatory pain (Lillesø et al, 2000). We previously found that the antinociceptive effect of morphine was markedly suppressed against mechanical allodynia in the inflammatory pain state (Aoki et al, 2014b). In the present study, we further characterized the antinociceptive effect of narcotic analgesics, including morphine, against thermal hyperalgesia in the inflammatory pain state, and found a special effect of methadone in restoring suppressed morphine antinociception in the inflammatory pain state.…”
Section: Introductionmentioning
confidence: 58%
“…We previously determined the antinociceptive effect of morphine against mechanical allodynia in the CFA-induced inflammatory pain state in mice using the von Frey filament test (Aoki et al, 2014b). In that study, the antinociceptive effect of morphine against mechanical allodynia was bilaterally suppressed at 1 and 4 days after CFA treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations